MISI PAULUS DALAM GALATIA 2:6-10: SATU INJIL YANG BENAR DAN PELAYANAN SOSIAL - Sarni Hasang (Sekolah Tinggi Teologi Excelsius, 2022)
This article will be based on Galatians 2:6-10 as it discusses Paul's mission as it relates to bringing people to the truth. Based on a text analysis approach based on syntax and semantics, which focuses on the verse. The text will interact with the thoughts of the Church Fathers. Mission is the main message of the gospel message. Because the gospel is the foundation of the church. But the reality is that the ministry is not only conveying the truth but also caring for the poor. The literature that the author uses is exegesis of the text. The author who specifically explores this topic by doing exegesis based on the four layers of meaning in the scriptures. This letter is Paul's most prominent mission letter in the NT. The topic of Paul's mission in this paper is studied using the method of exegesis. Paul's mission in Jerusalem emphasized the one true gospel and social service. The discussion of the word study only focuses on the true gospel that brings people to salvation. Moreover, discussions like this prove that the true gospel is the gospel that brings salvation. The purpose of the author uses the method of semantic exegesis to formulate Paul's mission according to the Galatians. This study has implications for the congregation in Indonesia in the context of community and church life. In the context of community life, the congregation increases a sense of concern for others through the practice of living that becomes a light for the world. Keywords: Paul's Mission in Jerusalem, Paul Affirms One Gospel, Paul's Social Service.